Tipos de fertilizantes biorgánicos y químicos en el crecimiento inicial de Caryodendron orinocense H. Karst. "metohuayo" y Cedrelinga cateniformis D. Ducke. "tornillo". Puerto Almendra, Loreto - Diaz Sevillano, Paulo Francesco (2022)
The study was conducted at the "Fundo Almendra", property of the National University of the Peruvian Amazon (UNAP), located in the town of Puerto Almendra, district of San Juan Bautista, province of Maynas, Loreto region (9576945 N, 680112 E). The main objective was to determine the effect of biorganic and chemical fertilizers on the initial growth of Caryodendron orinocense H. Karst. "metohuayo" and Cedrelinga cateniformis D. Ducke. "tornillo". The statistical design was a Randomized Complete Block Design (RCBD) with four replications in a 1-hectare agroforestry system with the treatments: T1= organic substrate (gallinaza-black earth+sand), T2= SO + 100 g NPK (20-20-20), T3= SO + 100 g Phosphoric Rock, T4= SO + FBO (Bio-Organic Fertilization). The results show that in the two forest species there is an increase in the initial growth in plant height, stem diameter and number of leaves, but there is not enough significant statistical evidence of the fertilizers on the initial growth behavior in these species.